Addendum: The prevalence and distribution of the flexor carpi radialis brevis muscle in the Turkish population - Akkoc, R.F.; Aksu, F.; Emre, E.; Ogeturk, M. (NLM (Medline), 2022)
[Abstract Not Available]
Keywords: Animals; Forearm; Forelimb; Muscle, Skeletal; Prevalence; animal; forearm; forelimb; prevalence; skeletal muscle